Anxiety and Psycho-Physiological Stress Response to Competitive Sport Exercise - Tanguy, Gaelle; Sagui, Emmanuel; Fabien, Zagnoli; Martin-Krumm, Charles; Canini, Frédéric; Trousselard, Marion (Frontiers in Psychology, 2018)
introduction Regular sport practice is recognized as beneficial for health. In certain situation of practice, namely selective exercise, it nevertheless appears likely to induce a stress response. Anxiety is a stress response-modulating factor. Our objective is to characterize the role of anxiety in the stress response induced by a selective race. Method 63 young male military conducted a selective race (an 8 km commando-walk) and were assessed the day before, the day of the race and the day after. The variables were psychometric (anxiety- trait, state and mood, stress adjustement (coping), and perceived stress and physiological nocturnal stress biomarkers (heart rate variability and sleep actigraphy). The subjects were classified on the basis of anxiety questionnaires, using mean-k clustering, into two groups according to their anxious (G ANX) or non-anxious (G N-ANX). Results Before the race, the G ANX was characterized by a lower level of self-esteem, higher scores in dysfunctional coping and a greater perceived stress compared to the G N-ANX. Compared to G N-ANX, the stress response to the exercise was higher in G ANX: G ANX exhibited (1) in immediate post-exercise, greater level in mood-anxiety and -anger and mental fatigue associated with a same level of physical fatigue and (2) in nocturnal post-exercise, an increase in sympathetic activation associated with a higher sleep fragmentation. Conclusions A selective race causes a stress response, particularly for anxious subjects. Repetition of selective sport exercises for anxious status could be at risk for health, namely by increasing the risk of emergence of overtraining. These results must be taken into account for professional anxious athletes by highlighting their need of anxiety management program.